Enterprise engineering : sustained improvement of organizations - Janssen, Theo (Springer, 2016)
This book provides a fundamental and practical introduction to Enterprise Engineering, demonstrating how to employ this approach to map the essence of an organization at the core level of internal cooperation. It then explains how, based on these insights, organizations can benefit from opportunities for improvement that would have otherwise gone unnoticed. Further, the book explains how to adapt the structure of an organization to the needs of its management and offers valuable tools for improving and perfecting it, along with guidelines on implementing profound and sustainable organizational changes. The examples and cases it presents show an increase in efficiency of up to 70% and increases in productivity and sales performance of more than 40%, once the flaws in an organization's structure have been identified and resolved.- Resumé vydavatel
Keywords: organizační změna; strategický management; podniky; reengineering; organizational change; strategic planning; business enterprises; reengineering (management); monographs; electronic books; monografie; elektronické knihy